Lifelong Education Programs and Community Welfare: A Case Study of Salimah in Pela Mampang - Dwitya Paramita; Syahida Rena; Muh. Ubaidillah Alghifary Slamet (Universitas Islam negeri Mahmud Yunus Batusangkar, 2024)
This study aims to analyze the implementation of lifelong education programs in improving community welfare through a case study of the Salimah mass organization in Pela Mampang, South Jakarta. Lifelong education is conceptualized as a continuous and inclusive learning process that extends throughout the life span and plays a strategic role in addressing socio-economic challenges in urban communities. This research employed a qualitative case study approach, with data collected through in-depth interviews, non-participant observations, and document analysis involving organizational leaders, educators, volunteers, and program participants. The findings reveal that Salimah implements various non-formal lifelong education initiatives, including religious education, parenting education, women’s empowerment, entrepreneurship training, and elderly education programs. These initiatives contribute to strengthening economic capacity, social cohesion, family resilience, and community participation. Supporting factors include a well-structured organizational system and strong community engagement, while limited funding and reliance on volunteer resources remain key challenges. The study concludes that community-based lifelong education programs can effectively complement formal education systems and function as a multidimensional strategy for enhancing community welfare in urban settings.